Reverse logistics of medicines; Case study in the municipality of Belém-Pará - Dias, Jaqueline Medeiros; Leocadio, Sonia Rodrigues; Freitas , Andrei Junior do Nascimento; Lopes, Maria do Socorro Bezerra; Martins, Maria de Nazaré Rodrigues Pereira; Almeida, Thais Monteiro Goes; Chaves, Andrea Fagundes Ferreira (Seven Editora, 2023)
The inadequate disposal of medications has serious ramifications, such as ecosystem aggression, water and soil pollution, and posing a risk to the health of humans and animals. The implementation of Medication Reverse Logistics (LR) constitutes a remarkable technological progress for the pharmaceutical industry, as it not only fulfills their responsibilities but also plays a crucial role in reducing hazards to public health and the environment. This study aims to investigate how LR is being implemented in the disposal of expired or unused medications in pharmacies, as well as the perception of the residents of Belém, PA. The methodology employed was a descriptive field study using questionnaires, with data collected through structured interviews conducted in person with pharmacists and a remote survey with consumers on the subject. The results of the applied research showed that, according to pharmacy networks, LR practices are adopted as a result of environmental and sanitary requirements. Furthermore, the research indicated that 100% of the networks inform their customers about the importance of LR-related practices. Regarding the final destination, they reported that 80% of pharmaceutical waste is incinerated. Among the surveyed population, it was found that 70.16% of expired or unused medications are disposed of in regular trash, while 3.49% are flushed down the toilet. It was also observed that 62.02% of consumers have never found any collection points in the pharmacies they frequent, and 96.12% responded that they have never received any information regarding the proper disposal of medications. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-132